Danish guidelines on management of otitis media in preschool children. (August 2016) - Heidemann, C.H.; Lous, J.; Berg, J.; Christensen, J.J.; Håkonsen, S.J.; Jakobsen, M.; Johansen, C.J.; Nielsen, L.H.; Hansen, M.P.; Poulsen, A.; Schousboe, L.P.; Skrubeltang, C.; et al.
Abstract: Introduction: Otitis media is one of the most common diseases in small children. This underlines the importance of optimizing diagnostics and treatment of the condition. Recent literature points toward a stricter approach to diagnosing acute otitis media (AOM). Moreover, ventilating tube treatment for recurrent AOM (RAOM) and chronic otitis media with effusion (COME) has become the most frequently performed surgical procedure in pre-school children. Therefore, the Danish Health and Medicines Authority and the Danish Society of Otorhinolaryngology, Head and Neck Surgery deemed it necessary to update the Danish guidelines regarding the diagnostic criteria for acute otitis media and surgical treatment of RAOM and COME. Methods: The GRADE system (The Grading of Recommendations Assessment, Development and Evaluation) was used in order to comply with current standards of evidence assessment in formulation of recommendations. An extensive literature search was conducted between July and December 2014. The quality of the existing literature was assessed using AGREE II (Appraisal of Guidelines for Research & Evaluation), AMSTAR (assessing the Methodological Quality of Systematic Reviews), QUADAS-2 (Quality of Diagnostic Accuracy Studies), Cochrane Risk of Bias Tool for randomized trials and ACROBAT-NRSI (A Cochrane Risk of Bias Assessment Tool for Non-Randomized Studies). The working group consisted of otolaryngologists, general practitioners, pediatricians, microbiologists and epidemiologists. Conclusion: Recommendations for AOM diagnosis, surgical management for RAOM and COME, including the role of adenoidectomy and treatment of ventilating tube otorrhea, are proposed in the guideline.